Wagnerovy punčošky v léčbě vývojové dysplazie kyčelního kloubu, časně diagnostikované v rámci všeobecného skríninku - Pach, Miroslav; Kamínek, Petr; Mikulík, Josef (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2008)
Developmental dysplasia of the hip (DDH) is a serious anatomical abnormality. The aims of the study were to compare the current views on general screening for DDH and, in a group of patients diagnosed for DDH both clinically and ultrasonographically, to analyse the results of their treatment with Wagner stockings. MATERIAL AND METHODS: In the years 2000 to 2001, a total of 3,221 children were examined at birth clinically and by ultrasonography using Graf's method. DDH was diagnosed in 137, and Wagner stockings were used for treatment in 127 patients. This Wagner abduction device consists of linen stockings buttoned to a linen baby shirt. It is based on the Pavlik harness treatment of DDH, and enables us to start therapy at neonatal age. The group was followed up, with checkups including clinical examination and AP radiography to evaluate position of the femoral head in relation to avascular necrosis (AVN) by the Salter method. The data obtained was statistically analysed by the SPSS software, version 14 (SPSS Inc., Chicago, USA). RESULTS: Out of the 127 children, 106 (95 girls and 11 boys) completed the treatment. In 87 (82%) children with Wagner stockings only, the treatment took place for an average of 82 days (range, 28 to 167), with abduction therapy starting on average at 13 days (range, 1 to 76 days). In 19 (18%) children it was necessary to continue abduction therapy and Wagner stockings were replaced by a Pavlik's harness. The total abduction treatment then lasted on average for 152 days (range, 81 to 289). After January 1, 2005, 75 children (follow-up rate, 70.7%) were examined, 33 at regular checkups and the rest at invitation. The average follow-up was 5.9 (3.8-7.5) years. On two early radiograms with left-side findings, proximal femoral lesions met the Salter criteria of AVN diagnosis. The AVN rate was 2.6% or 1.8% when related to either the patients or the affected hips. At the latest follow-up even in these cases the radiographic findings were resolved. DISCUSSION: At present there is no consensus concerning either screening of newborns for DDH or its early therapy. In the Czech Republic the general screening known as three-step examination of infant hips attained a legal frame by the Regulation issued by the Ministry of Health in 1977 and its amendment in 1996. In Austria the general clinical and ultrasonographic screening is regarded as the gold standard. On the other hand, some official bodies such as the U.S. Preventive Services Task Force, American Academy of Pediatrics or Canadian Task Force do not recommend any general screening.The results of this retrospective study were compared with those of treatment with the Pavlik harness or Frejka pillow, which are both based on a passive mechanical mode of therapy. The comparison has shown that the treatment with Wagner stockings is highly effective and has a low AVN rate. CONCLUSION: This retrospective study has shown that, in DDH, therapy with Wagner stockings is sufficient to provide for physiological development of the hip, while the AVN rate is very low. Early diagnosis and treatment related to general screening are both beneficial. Based on these results we recommend Wagner stockings as a useful aid in the treatment which is initiated early in infancy and is in agreement with the Pavlik method of functional DDH therapy.
Keywords: ženské pohlaví; mužské pohlaví; protetické prostředky; Orthotic Devices; Humans; novorozenec; Hip Dislocation, Congenital; Infant; Infant, Newborn; Male; kojenec; lidé; Female; vývojová kyčelní dysplazie; novorozenecký screening; Neonatal Screening